Integration of Pancasila Student Profile Values in Islamic Religious Education (PAI) Learning at SMA Negeri 1 Gerung - Sadri Sadri; Emawati Emawati; Hully Hully (Yayasan Adra Karima Hubbi, 2024)
Background. The profile of Pancasila students is a manifestation of the preparation of the nation's next generation who are capable and qualified to face changing times while maintaining the values of Pancasila. Purpose. The purpose of this research is to analyze the integration of Pancasila student profile values in learning Islamic Religious Education (PAI) in Senior High Schools (SMA). Method. This research method uses qualitative research with data collection techniques using interviews, observation and documentation. Data analysis was carried out in three stages, namely data reduction, data display and conclusion drawing. Results. The results of this study indicate that the integration of Pancasila learner profile values in learning Islamic Religious Education (PAI) in this Senior High School (SMA) includes six indicators, namely faith, fear of God Almighty and noble character, global diversity, mutual cooperation, independence, critical and creative reasoning. In integrating the values of the Pancasila student profile in learning Islamic religious education in this high school there are also several obstacles faced such as the lack of mastery of teacher competencies and teaching skills, student delinquency, unhealthy social environment and lack of parental attention. Conclusion. While the solution is to provide the opportunity to continue their education at a higher level, participate in scientific activities, instill good habits in students, create a religious, healthy, safe and comfortable school environment for students and improve cooperative relations between schools and parents.